"Anyone else? Is this normal?": anonymously seeking information on the Ovia Pregnancy App. Issue 1 (1st January 2023) - Ortiz Juarez-Paz, Anna V.; Doherty, Eileen F.; Storch, Sharon L.; Kallis, Rhiannon B.; Kleinman, Steven B.
ABSTRACT: Women often experience anxiety and a desire for information before, during, and after their pregnancy. While women have traditionally turned to their doctors, family, and friends, the Internet and mobile devices offer options such as search engines and online pregnancy forums to meet their information needs. Additionally, pregnancy apps provide a convenient new way for women to connect and exchange information. This study explored the Community feature of the Ovia Pregnancy app to understand how, and in what context, anonymous users engage with each other and utilize the app to seek information. A content analysis of posts reveale d users were most likely to share their experiences of pregnancy and/or seek medical information. Users frequently sought reassurance from other Ovia users regarding the normalcy of their pregnancy and affirmations regarding health questions. The affordances of anonymity and accessibility found within the Community feature of Ovia Pregnancy potentially lowered users' inhibitions to ask seemingly embarrassing health questions and allowed them to receive responses in a timely manner. Future studies should assess women's motivations for using the Community feature of the app and assess the quality of medical information exchanged.